Protective effects of alpha-lipoic acid against oxidative injury in TNBS-induced colitis - (:unkn) unknown (My University, 2009)
Purpose: Alpha-Lipoic acid (ALA), which has been intensely investigated as a therapeutic agent for several diseases, is elucidated for its possible protective effect as a potent antioxidant on colonic inflammation. Material and Methods: Following intracolonic administration of trinitrobenzene sulphonic acid, Sprague-Dawley rats were treated orally either with saline or ALA (100 mg/kg/day), for three days. On the 4th day, rats were decapitated and distal colon was removed for the macroscopic and microscopic damage scoring, for the measurement of malondialdehyde (MDA), glutathione (GSH) and collagen levels, myeloperoxidase (MPO) and Na+ - K+ -ATPase activity, luminol and lucigenin chemiluminescences (CL) and oxidant-induced DNA fragmentation. Lactate deydrogenase (LDH) activity, TNF-α, IL-1β, IL-6 and antioxidant capacity (AOC) were assayed in blood samples. Results: Colitis caused significant increases in the colonic macroscopic and microscopic damage scores, MDA, and collagen levels, MPO activity and CL values, along with a significant decrease in tissue GSH level and Na+ - K+ -ATP ase activity. Similarly, serum cytokines as well as LDH were elevated in the vehicle-treated colitis group as compared to control group. On the other hand, ALA treatment reversed all these biochemical indices, as well as histopathological alterations induced by TNBS. Conclusion: ALA protects the colonic tissue via its antioxidant and membrane stabilizing properties.
Keywords: Alpha lipoic acid; Colitis; Cytokines; Glutathione; Tumor necrosis factor-alpha